THE EFFECT OF DIFFERENT CULTURE MEDIA ON IN VITRO FERTILIZATION OF MICE - Ibrahim, Mohammed A; Al-Ahmad, Hazim I; Mohammed, Wasnaa H (Al-Nahrain Journal of Science, 2018)
The effect of different types of media on in vitro fertilization (IVF) of mice oocyte wasinvestigated. IVF was carried out in RPMI-1640 medium at recommended temperature (37 C) andpH (7.4). The obtained results showed that 63.73% of used oocytes were fertilized, and thepercentage of abnormal embryos was 27.58%. While, using other culture media at sametemperature and pH, gave low percentage of fertilization and higher yield of abnormal embryos.Thus, using Medicult IVF, Earl s and TCM-199 were gave fertilization percentages equivalent to38.75, 42.42 and 61.45% respectively; whereas, the percentages of abnormal embryos were 32, 35.7and 33.89 % respectively.The reported results indicate that composition of various types of culture media have significanteffect on the rate of fertilization and abnormal embryos.